Treść ekonomiczna zdarzeń gospodarczych - Hellich, Ewa (Economic Issues of Accounting Events, 2005)
Accounting Events - the business end economic activities which a financial reporting system seeks to measure end report. The bulk of accounting events that flow through the books will be exchange transactions. These are rather obvious and tend to command attention. However, accrual accounting, which is based on the matching principle, will also necessitate recognizing many important accounting events which do not necessarily have an exchange transaction. This is where more thought is required and where the accounting art comes into its own. It is worth bearing in mind what is not an accounting event. Practical considerations, such as cost, objectivity and verifiability, necessarily limit what an accounting system can measure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 63-71